Hybridization of an s-wave impurity with graphene lattice - Nghiem, Hoa; Pham, Lam; Nguyen, Linh; Đặng, Hùng Thế (Communications in Physics, 2024)
Hybridization function is a quantity characterizing electron hoppings between an impurity and a host material in which the impurity resides, a full understandinging of it is crucial for studying correlation effects in various impurity problems. This work studies the hybridization function for the Anderson impurity model describing a single-orbital impurity on a honeycomb lattice simulating graphene and presents a calculation approach to obtain this function at low energy. Within this approach, the general form of the hybridization function in graphene is presented and analytical expressions of low-energy hybridization spectrum are obtained. The results quantitatively match numerical solutions for different impurity positions on the lattice. The effect of the low-energy hybridization spectrum and the capability to predict the correlated effects of the impurity problem are discussed thoroughly, suggesting that different types of pseudogap Kondo effect may occur at different impurity positions.